MAP 65-is it enough?. Issue 2 (3rd April 2022) - Hu, Yaqi; Lim, Aaron
Abstract : Purpose of review: The purpose of this review is to look at the current evidence on the consequences of intraoperative hypotension and discuss improvements that can be implemented for its prevention. Recent findings: Literature continues to supply convincing evidence that even brief periods of intraoperative hypotension are associated with increased perioperative morbidity and mortality. Recent randomized controlled trial showed intraoperative early use of vasopressor and maintaining blood pressure within tight ranges improves outcomes. Summary: There should be a shift in paradigm in focusing on the prevention of intraoperative hypotension instead treatment. The suggested goals to help maintaining hemodynamic stability during anesthesia include ensure adequate blood pressure and flow; hypotension prevention; and ensure adequate anesthetic depth without overdose.